PERAN BAHASA ACEH DALAM MEMPERTAHANKAN IDENTITAS BUDAYA DI ERA GLOBALISASI - Putri Aoulia, Bintang Rizki (Jurnal Society : Pengamat Perubahan Sosial, 2024)
Language is an important element in society where language itself is a symbol of community identity in an area. People living in Aceh province usually use their regional language, Acehnese language, where this language is a mother tongue that has been passed down or inherited by their ancestors. Therefore, in this topic, the role of the Acehnese language in maintaining the cultural identity of the Acehnese people in the era of globalization will be discussed, and what efforts and challenges are faced in preserving the regional language itself. The method used is a qualitative method with a literature study approach. Based on the findings that have been made, the Acehnese language plays a very important role in maintaining the cultural identity of its people in the current era of globalization, where the Acehnese language itself contains moral values, customs used by the community as a philosophy in life and society.